Determinants of environmental disclosures: Green initiatives by listed companies in Malaysia - Ismail, Fathinah; Mohamed, Zulkifli; Mohd Saad, Noriza (Journal of Islamic, Social, Economics and Development, 2025)
In an era of heightened emphasis on sustainability and transparency, it is essential to understand the factors that drive effective environmental disclosure to advance Environmental, Social, and Governance (ESG) practices. This study aimed to identify the determinants of environmental disclosure and assess the impact of firm size, leverage, liquidity, profitability, and stakeholder engagement score on environmental disclosure, both collectively and individually, within the context of ESG green initiatives among corporate companies listed on Bursa Malaysia for the period 2020 to 2024. The data analysis, involving 357 companies, was conducted using panel regression analysis and the analysis was performed with EViews 13. The findings indicated that firm size, leverage, liquidity, profitability, and stakeholder engagement score significantly impact environmental disclosure when considered together. However, when examined separately, only firm size, profitability, and stakeholder engagement score show a notable partial effect on environmental disclosure, while leverage and liquidity do not significantly influence environmental disclosure. These results highlighted the importance of certain firm characteristics and stakeholder engagement in driving corporate transparency and accountability in environmental reporting. This study has provided valuable insights for improving environmental reporting and integrating sustainability into corporate strategies, offering practical implications for policymakers, corporate leaders, and investors seeking to promote robust ESG practices.